The Effect of Inquiry Learning Model with Pictorial Riddle Method on Students' Creative Thinking Ability - Aulia Rahma Wardani; Syifaul Gummah; Sukainil Ahzan (Lensa: Jurnal Kependidikan Fisika, 2019)
This study aims to determine the effect of inquiry learning models with pictorial riddle methods on students' creative thinking abilities. This research is a quasi-experimental (Quasy Experiment) with Nonequivalent Control Group Design. The research sample consisted of two classes, namely class X IPA 2 and class X IPA 3, each of which amounted to 30 students. The creative thinking ability test instrument consisting of 12 items and observation sheets was used to collect data in this study. The results of the study were analyzed using SPSS v-22 software for windows. The results showed that: 1) the average initial test scores of the experimental and control classes were 45.7 and 44.1 respectively; 2) the average initial test scores of the experimental and control class were 79.2 and 68.8 respectively; 3) homogeneity prerequisite tests show homogeneous data and normality tests show normally distributed data; 4) t-test results obtained Sig. (2-tailed) posttest data (0.00) is smaller than alpha testing (0.05), so the working hypothesis (Ha) is accepted. Thus, the inquiry learning model with the pictorial riddle method influences students' creative thinking abilities.